Branding Religion and Culture: A Multimodal Analysis of Sedaap and Indomie Ramadan Advertisements in 2025 - Sutarman, Sutarman; Adiwinata, Akbar; Abdusamad, Zainudin; Rahmawati, Lela (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study investigates how religious and cultural values are embedded in Indonesian Ramadan advertisements through Multimodal Discourse Analysis (MDA). The research focuses on the 2025 campaigns of two prominent instant noodle brands, Sedaap and Indomie, which utilize verbal, visual, and auditory elements to construct persuasive narratives. The study aims to examine how Islamic symbols, national identity, and familial values are communicated through these multimodal resources. Using frameworks from Kress, G., & van Leeuwen, (2006) and theories on pious consumerism and cultural discourse, the findings reveal that the advertisements serve not only as promotional tools but also as cultural texts that reflect and shape Muslim identity. Sedaap emphasizes youthful, pop-cultural appeal, while Indomie presents emotional narratives rooted in gratitude and togetherness. The study concludes that commercial branding during Ramadan actively contributes to the construction of religio-cultural ideology in modern Indonesia. These insights offer implications for media literacy, religious communication, and branding ethics.